MANFAAT KANDUNGAN ALKOHOL NIRA - AREN TERHADAP PENYAKIT DIABETES MELLITUS - Martinus Martinus Telaumbanua (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
This service aims to provide information to the public regarding to describe how the effect of palm tree alcohol content on diabetes mellitus, as well as alertness on the level of sap consumption in diabetes mellitus sufferers in terms of the benefits of alcohol content contained in palm sugar. The research study method that the author uses is the Research Report (Field Research), namely data obtained through direct observation and observation of the object of study and the distribution of questionnaires involving various sources, experts, and staff obtained. The conclusion is that the palm tree is one of the balancing plants for the ecosystem and rural ecology. The alcohol content in sap is in accordance with the experience and views of the community that the alcohol content of sap can reduce glucose levels for people with diabetes mellitus (sugar disease). The palm tree that produces sap and turns out to be multipurpose, from the roots to the fruit, provides various benefits for human life.